Effects of Intrathecal Midazolam (1mg) with Hyperbaric Bupivacaine 0.5% (15 Mg) for Spinal Anesthesia for Cesarean Section in Obstetrics Patients - Ishtiaq Ahmad, Sahibzada Adnan Ahmad, Khadija Akbar, Umbrin Naz, Muhammad Javed Khan, Shahid Maqsood (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Intrathecal administration of adjuvant agents such as midazolam has been shown to enhance the quality and duration of spinal anesthesia. This study evaluated the effects of intrathecal midazolam (1 mg) in combination with hyperbaric bupivacaine 0.5% (15 mg) on intra- and postoperative outcomes among obstetric patients undergoing cesarean section. Methods: A total of 220 parturients scheduled for elective or emergency cesarean delivery under spinal anesthesia were included in this prospective, randomized observational analysis. Demographic variables (age, parity, ASA class, gestational age, BMI, previous cesarean section, comorbidities) and clinical outcomes (onset of sensory block, duration of analgesia, sedation score, incidence of shivering, nausea, and hypotension) were recorded. Cross-tabulation with Chi-square testing and logistic regression were performed to identify predictors of intraoperative hypotension and other outcomes. Results: Most participants were aged 25–34 years (73%) and ASA II (65%), with 60% undergoing elective procedures. The mean duration of analgesia was 216 ± 45 minutes (95% CI 209–223). Hypotension occurred in 28%, shivering in 25%, and nausea in 30% of cases. Chi-square analysis showed significant associations between BMI and hypotension (p = 0.021), ASA class and hypotension (p = 0.037), and age with duration of analgesia (p = 0.031). Logistic regression identified BMI (B = 0.78, SE = 0.32, OR = 2.19, 95% CI 1.13–4.25, p = 0.021) and ASA class (B = 0.65, SE = 0.31, OR = 1.91, 95% CI 1.04–3.50, p = 0.037) as independent predictors of hypotension. Conclusion: Intrathecal midazolam (1 mg) combined with hyperbaric bupivacaine 0.5% (15 mg) provides effective spinal anesthesia for cesarean delivery, prolongs postoperative analgesia, and improves sedation with a modest incidence of adverse effects. Patient BMI and ASA class are significant predictors of intraoperative hypotension and should be considered in anesthetic planning. Keywords: Intrathecal midazolam, Bupivacaine, Spinal anesthesia, Cesarean section, Obstetric anesthesia, Hypotension, Sedation, Analgesia duration